Ten-year clinical performance of zirconia posterior fixed partial dentures - Matta, Ragai; Eitner, Stephan Frank; Stelzer, Simon Paul; Reich, Sven; Wichmann, Manfred; Berger, Lara (Journal of Oral Rehabilitation, 2021)
Background: With the constantly increasing demand for metal-free solutions in dental therapy, numerous ceramic restorations have found their way into everyday clinical practice, but long-term clinical data are limited. Objective: The aim of this prospective clinical study was to evaluate three- and four-unit fixed partial dentures in the posterior region made of zirconium dioxide frameworks veneered with feldspathic porcelain after 10 years in clinical use. Methods: Based on the two studies published in 2009 and 2012, in which the all-ceramic FDPs were evaluated after 3 and 5 years of function, a clinical evaluation of a total of 17 restorations after 10 years with regard to their condition and long-term stability was carried out in the course of this study. The restorations were fabricated using feldspathic ceramic-veneered, yttria-stabilised, tetragonal zirconium dioxide as the framework material. The data collection was based on modified CDA criteria and included, for example, the shape, shade, surface condition and the success and survival rates of the restorations. Results: The all-ceramic prostheses embodied excellent biocompatibility and colour reproduction. As a result of an increased incidence of chipping fractures, the success rate was 60%. The survival rate, however, was 88.2%, as 2 of the 17 restorations were lost. Conclusion: All-ceramic concepts for FDP constructions in the posterior region achieved satisfactory results in terms of durability after 10 years. The main problem was chipping, as has been generally recognised. Nevertheless, the materials were characterised by excellent aesthetics and biocompatibility, which ultimately makes them a good alternative to conventional restorative options. Trial registration: This study is registered in DRKS—German Clinical Trials Register with the register number DRKS00021743.
CRIS-Team Scopus Importer:2021-11-19
Keywords: ceramics; dental porcelain; fixed partial denture; survival analysis; zirconium; zirconium oxide